PEMIKIRAN RAHASIA HUKUM ISLAM DALAM RUANG PUBLIK (HUQUQ ALLAH) - Fikri Fikri (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
As generally, syarak is concist of two parts, the worship and muamalat. The part of worship has characteristic that can answer or give solve the problem is Allah and his prophet. Otherwise, the part of muamalat has characteristis that answer or solve is human. By the mapping of the two different dimensions, there is the formula of jurists who say that if the dimension of worship, basically can’t apply the rules unless there is a law ordered it. Compare the dimension of muamalat that basically muamalat can apply the rules if there is a legitimate legal forbidden it.